Intellectual property protection indicators in global software development (Research, Society and Development, 2020)
One of the great challenges is to establish mechanisms for monitoring the protection of intellectual property in global software development. Thus, the use of information on technology service monitoring tools can provide selection criteria by client companies. The work was carried out to select indicators and parameters related to the maturity of intellectual property in global software development. To better chose these indicators, the methodology was adapted to provide the monitoring of the maturity of the protection of Intellectual Property in Information Technology Services. Information from the scientific and technological literature and the information obtained from a structured questionnaire applied to actors working on IT services were used. The quantitative approach and structural equation modelling (SEM) were used for a sample of 19 IT professionals. The data analysis showed a positive relationship between IT governance and project (H1) and Project and contract (H2). As a result, 25 indicators were selected as potentially favorable for monitoring maturity in IP protection.